نظام الحوافز في الوظيف العمومي في الجزائر - واسع, عمار (جامعة الوادي -University eloued, 2017)
حاولت دراسة نظام الحوافز في الوظيف العمومي ،تشخیص الواقع الفعلي لظاھرة الحوافز والأداء في المؤسسات العموميه بالجزائر، وقد تعرضت الدراسة إلى مختلف الاتجاھات والمداخل النظریة والأبحاث التي عالجت مسالة التحفیز كمتغیر تنظیم يیرتبط بباقي متغیرات البناء التنظیمي للمؤسسة. وقد سعت الدراسة إلى تقصي العلاقات القائمة بین مختلف أنواع الحوافز التي تقدمھ االمؤسسة وأداء العاملين، وناقشت عدد من المتغیرات التي شكلت محور اھتمام نظریات التنظیم.وضمن ھذا السیاق طرحت الدراسة فرضیة عامة حول التحفيز كوسيله او نمط تعتمده الاداره او المؤسسه للتاثير على الفرد وتوجيه سلوكه لىتحقيق اهدافها وللبرھنة والتأكد من العلاقات القائمة بین الحوافز المادیة ومستوى الأداء ، لدى العاملين وبین الحوافز المعنویة ومستویات الرضا والاستقرار في العمل ،وقد اعتمدت الدراسة في تحقیقھا لأھدافھا وتقصي فروضھا على المنھج الوصفي وقد توصلت ھذه الدراسة إلى جملة من النتائج والمتمثلة في أن قیمة الحوافز المادیة التي تقدمھا المؤسسة یرتبط ارتباطا وثیقا بمستوى الأداء الوظیفي لدى العاملين وأن الموظفين في المؤسسة العمومیة یتلقى أجرا منخفضا ومكافآت ضعیفة ،الأمر الذي خلق لدیھ امشاعر عدم الرضا والارتیاح في العمل الأمر الذي انعكس سلبا على أدائه ،كما أن الحوافز المعنویة بأبعادھا الثلاثة : المشاركة في اتخاذ القرار والترقیة والتدریب تؤثر على مستوى الرضا الوظیفي واستقرار العمال، حیث أسفرت الدراسة على أن اختلال نظام الحوافز المادیة خاصة الأجر وعدالة معاییر توزیع المكافآت والعلاوات المادیة یثبط دافعیة العمال لبذل مجھودات اكبر، في حین أن عدم إشراك العمال في اتخاذ القرارات الخاصة بعملھم وعدم إتاحة فرص حقیقیة للتدریب و التكوین یفضي إلى عدم ارتیاحهم الأمر الذي ینعكس سلبا على أداءھم ،كما أن عدم فعالیة نظام الحوافز وعدم استجابتھ المتطلعات الموظفين في المؤسسة تؤدي إلى الإحباط وعدم استقرارهم في عملھم .. وفي الأخیر یتضح أن ھناك ارتباط وثیق بین الحوافز المقدمة من طرف المؤسسة وبمختلف أنواعھا ومستوى الأداء لدى المؤسسات العموميه ،وأن انخفاض أداء العاملين یعود بالأساس إلى عدم وجود نظام حوافز فعال یشبع الحاجات المختلفة للأفراد ،والذي ینعكس سلبا على نوعیة الخدمات بصفة عامة. I tried to study the system of incentives in public employment, to examine the actual reality of incentives and performance Public institutions in Algeria, and the study was subjected to different trends and approaches Theory and research that addressed the issue of catalysis as an organizational variable related to the rest of the building variables The study sought to investigate the relationships between different types of incentives provided by the institution and performance And discussed a number of variables that formed the focus of attention to regulatory approaches. Within this context, the study presented a general hypothesis on motivation as a method adopted by management or institution to influence the individual and guide his behavior to achieve its objectives And to ascertain the relationships between material incentives and performance levels of employees And between the moral incentives and the levels of satisfaction and stability in work, and the study has been adopted to achieve them For its objectives and to investigate its hypotheses on the descriptive approach as it has been used This study concluded that the value of the material incentives offered by the institution Is closely related to the level of job performance of employees and staff in the organization The public receives low wages and low wages, creating dissatisfaction And relaxation in work, which reflected negatively on performance, and moral incentives in the three dimensions: Participation in decision-making, promotion and training affects the level of job satisfaction and the stability of workers, The study found that the system of material incentives, especially wages, and the fairness of the criteria for the distribution of rewards Material bonuses discourages workers from making greater efforts The lack of involvement of workers in making decisions about their work and the lack of real opportunities for training Formation leads to discontent, which is reflected negatively on their performance The effectiveness of the incentive system and its failure to respond to the expectations of the employees in the organization lead to frustration and lack Stability in their work .. Finally, it is clear that there is a strong correlation between incentives provided by the institution and its various types And the level of performance of public institutions, and that the decline in the performance of workers is mainly due to Lack of an effective incentive system that satisfies the different needs of individuals, which is reflected negatively on the quality of services in general
سياسة عامة
Keywords: نظام ، حوافز ، الوظيف العمومي ، أسباب ، أداء ، سلك الوظيف العمومي ، الحوافز المادية; system .stimulate . alozivpublique . reasons . wire alozivpublique .performance